Learning to reach health for all : thirty years of instructive experience at BRAC - Rohde, Jon E.; BRAC. (Dhaka : University Press, 2005)
Contributed articles.
Includes bibliographical references (pages [185]-194).
Keywords: BRAC; Rural health -- Bangladesh; Rural health services -- Utilization -- Bangladesh; Health surveys -- Bangladesh